French‐style genetics v. 2.0: The "e‐CohortE" project. Issue 4 (11th July 2019) - Stoeklé, Henri‐Corto; Bollet, Marc; Cobat, Aurélie; Charlier, Philippe; Bloch, Oudy Ch.; Flatot, Jérôme; Draghi, Clément; Tolyan, Valérie; Hervé, Christian; Desvaux, Pierre; Uzan, Laurent; Grynberg, Michaël; et al.
Abstract: In the digital age, a genetics cohort has become much more than a simple means of determining the cause of a disease. Two‐sided markets, of which 23andMe, Ancestry DNA and MyHeritage are the best known, have showed this perfectly over the last few years: a cohort has become a means of producing massive amounts of data for medical, scientific and commercial exploitation, and for genetic use in particular. French law does not currently allow these foreign private companies to develop on French national territory and also forbids the creation of similar entities in France. However, at least in theory, this same law does not preclude the creation of new types of cohorts in France inspired by the success of two‐sided markets but retaining features specific to the French healthcare management system. We propose an optimal solution for France, for genomic studies associated with multi‐subject questionnaires, still purely theoretical for the moment: the development, with no need for any change in the law, of France's own version of "Genetics v.2.0": "e‐CohortE." Abstract : It is the overall organization and functioning of this project . In the digital age, a genetics cohort has become much more than a simple means of determining the cause of a disease. Two‐sided markets, of which 23andMe, Ancestry DNA and MyHeritage are the best known, have showed this perfectly over the last few years: a cohort has become a means of producing massive amounts of data for medical, scientific and commercial exploitation, and for genetic use in particular. French law does not currently allow these foreign private companies to develop on French national territory and also forbids the creation of similar entities in France. However, at least in theory, this same law does not preclude the creation of new types of cohorts in France inspired by the success of two‐sided markets but retaining features specific to the French healthcare management system. We propose an optimal solution for France, for genomic studies associated with multi‐subject questionnaires, still purely theoretical for the moment: the development, with no need for any change in the law, of France's own version of "Genetics v.2.0": "e‐CohortE."